Addressing climate change concerns in pediatric health care settings: exploring parental and physician perspectives - Eena Lin; Mohammed Jawaad Hussain; Krystal Hunter; Elizabeth Cerceo (Environment International)
Introduction: In 2015, the American Academy of Pediatrics released a policy statement on pediatricians’ role in battling the damaging effects of the climate crisis on children, a particularly vulnerable population. However, pediatric healthcare providers report difficulties integrating these discussions into their clinical practices. We designed a survey to evaluate the perceptions of parents and pediatricians regarding the health impacts of climate change, with the goal of identifying key opportunities for education and engagement. Methods: In this cross-sectional study, anonymous surveys were distributed to parents at 5 pediatric outpatient clinics in Southern New Jersey. A second anonymous survey was digitally distributed to physicians at the same outpatient clinics. We measured responses using a 4-point Likert scale and conducted a descriptive analysis, including frequencies, percentages, and 95 % confidence intervals. Results: We collected 111 parent surveys and 37 physician surveys. Many parents and physicians reported feeling worried (somewhat or very much) about the impact of climate change on their child’s and patient’s physical (57.4 % for parents, 83.8 % for physicians) and mental (30.0 % for parents, 64.8 % for physicians) health. The top three areas of climate health concern among parents were air pollution, vector-carried diseases, and allergens and pollen. The top three concerns for physicians were air pollution, allergens and pollen, and food security.Pediatricians reported that a lack of time (89.2 %) and knowledge (70.3 %) reduced their willingness (somewhat or very much) to discuss climate change during visits. When asked about solutions, they responded that patient education materials (75.6 %), communication training (70.2 %), and continuing professional education (78.3 %) would facilitate climate counseling (somewhat or very much). Conclusions: Our results suggest that parents and pediatricians alike are concerned about the impact of climate change on child health. Additionally, pediatricians feel ill-equipped to integrate climate change education into their daily practices. Future efforts to provide additional resources to pediatricians can help both parents and patients face a worsening ecological climate.